Return to sports activity after postoperative septic arthritis in ACL reconstruction - Monaco, E.; Maestri, B.; Vadal, A.; Iorio, R.; Ferretti, A. (The Physician and Sportsmedicine, 2010)
Background Septic arthritis after arthroscopic anterior cruciate ligament (ACL) reconstruction is a rare but potentially serious complication. Several different options have been proposed to treat this condition. Our study aims to report the clinical, radiological, and sports activity results using our original protocol based on outpatient irrigation of the knee as well as parenteral and oral antibiotics. Methods From January 2001 to January 2009, 14 patients (all active in sports) were treated for postoperative septic arthritis of the knee after ACL reconstruction in our institute. The treatment protocol included outpatient irrigation of the knee and parenteral antibiotics, followed by oral antibiotics. Repetitive irrigation was performed if necessary. The average follow-up period for our series was 38 months (range, 8-54 months). Follow-up included International Knee Documentation Committee (IKDC) forms, radiographs, Tegner and Lysholm scores, and KT-1000™ arthrometric evaluation. Results Treatment of infection was successful in all cases. At final examination, pivot shift score was negative in 12 of 14 patients, and was > 1 in 2 of 14 patients, whereas the Lachman item score was negative in all cases. The mean postoperative Tegner score was 7, and 12 of 14 patients returned to the same sport at the same level after surgery. The mean Lysholm score was 96. Using the IKDC score, 12 of 14 patients were graded as group A, and 2 of 14 patients were graded as group B. The mean postoperative manual maximum KT-1000™ side-to-side difference was 2.5 mm. No significant bone tunnel enlargement was found when evaluating the patients` radiographs. Conclusion The treatment regimen previously described provides reliable results for this complication. There were no recurrences of septic arthritis or bone infection, and no further surgeries were required. The graft could be retained during treatment of septic arthritis. Almost all patients returned to the preoperative and preinfection sport at the same level.